Managing Migration: The Clash Between Solidarity and Sovereignty - Oręziak, Bartłomiej (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
This paper analyses migration law regulations adopted within the European Union, focusing on the benefits and costs of the unification process of EU law. It first provides an overview of policies on border checks, asylum, and immigration, tracing the evolution of relevant legal norms in EU primary law. It then examines how development directions are shaped, examining analysing key areas of secondary EU legislation and decision-making processes in light of primary law principles. Next, the chapter outlines the unification of EU standards to enhance cooperation, using the examples of the Dublin system, qualification, reception, and procedures. This forms the basis for assessing the benefits and costs of deeper cooperation through unification. The chapter concludes by evaluating whether the expenses borne by EU Member States outweigh the benefits of implementing unified legal regulations in areas such as the Dublin system, qualification, and procedures, and separately, the reception system, within the broader framework of border checks, asylum, and immigration policies.